2019
DOI: 10.1002/chem.201901069
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Lajollamycin B

Abstract: The first total synthesis of lajollamycin B, as tructurally novel nitro-tetraene spiro-b-lactone/g-lactonea ntibiotic, is described. The convergent synthesis involves the construction of the C8'-C11' nitrodienylstannane and its coupling with the segment prepared from the C1'-C7' w-iodo-heptadienoic acid and the right-hand heterocyclic fragment, which has been utilized for our previouss yntheses of oxazo-lomycinA.T he revisiono ft he geometry of the terminal D 10',11' -double bond from E to Z is also described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…9 However, in 2019 Hatakeyama et al reported rst total synthesis of lajollamycin B and its C10 0 geometric isomer. 15 Surprisingly, a spectroscopic comparison with data for 11 reported by Oh et al 9 found to be identical with unexpected isomer. Thus, Hatakeyama et al carefully reinvestigated Oh's 2D NMR spectroscopic data of 11 and unambiguously assigned NOESY spectra to both prepared isomers.…”
Section: Structural Elucidation Of Oxazolomycinsmentioning
confidence: 66%
See 4 more Smart Citations
“…9 However, in 2019 Hatakeyama et al reported rst total synthesis of lajollamycin B and its C10 0 geometric isomer. 15 Surprisingly, a spectroscopic comparison with data for 11 reported by Oh et al 9 found to be identical with unexpected isomer. Thus, Hatakeyama et al carefully reinvestigated Oh's 2D NMR spectroscopic data of 11 and unambiguously assigned NOESY spectra to both prepared isomers.…”
Section: Structural Elucidation Of Oxazolomycinsmentioning
confidence: 66%
“…According to these ndings Hatakeyama et al revised the initially assigned geometry of lajollamycin B from (10 0 E)-to (10 0 Z)-congurated double bond. 15 The last two members of oxazolomycin family were isolated, characterized and reported in 2017 by Koomsiri et al 10 Both structures were elucidated using HR-ESI-MS, UV and IR spectra, optical rotation, 1D and 2D NMR spectroscopy. Structure of oxazolomycin A2 (14) indicated close similarity to oxazolomycin A (1), but difference in chemical shis of the oxymethylene H 2 -16 was observed.…”
Section: Structural Elucidation Of Oxazolomycinsmentioning
confidence: 99%
See 3 more Smart Citations